Analysis of Macroeconomic Determinants of Exchange Rate Volatility in India - Mirchandani, Anita (International Journal of Economics and Financial Issues, 2012)
The Foreign Exchange Market in India has undergone substantial changes over last decade. It is imperative by the excessive volatility of Indian Rupee causing its depreciation against major dominating currencies in international market. This research has been carried out in order to investigate various macroeconomic variables leading to acute variations in the exchange rate of a currency. An attempt has been made to review the probable reasons for the depreciation of the Rupee and analyse different macroeconomic determinants that have impact on the volatility of exchange rate and their extent of correlation with the same. Keywords: Exchange Rate; Inflation; Interest Rate; Foreign Exchange Market; Current Account; Exchange Rate Volatility; International Trade. JEL Classifications: F31; F41